Seletividade e eficácia de herbicidas na cultura do mamão - Nascimento, Paula Gracielly Morais Lima do (Universidade Federal Rural do Semi-Árido, 2011)
This study had as objectives evaluate the efficacy and selectivity of herbicides for the cultivation of papaya. Two experiments were conducted in field conditions in WG FRUTICULTURA, Sitio Sumidouro, Barauna - RN. In the first the herbicides were applied in pre-emergence of the weeds, before transplanting the papaya seedlings, being evaluated the following treatments: ametryn, diuron, ametryn+diuron, flumioxazin, isoxaflutole, two more witnesses, with and without weeding. At 7, 14, 21 and 28 days after the application of herbicides were realized visual evaluations of intoxication in papaya plants. At 0, 30, 45, 60 and 75 days after the application, evaluations were carried out for plant height and stem diameter. And at 21.42 and 63 days after the application evaluations were carried out on the mass of dry matter of weeds. The ametryn herbicides, diuron, flumioxazin, and the mix of diuron+ametryn, caused severe toxicity in papaya plants, causing them to die. The isoxaflutole caused intoxication in papaya seedlings that showed recovery at the end of the trial period. The weed interference resulted in papaya plants with smaller diameter of the stem, although the height of plants was not influenced. In the second experiment were evaluated eight herbicides (glyphosate, glufosinate-ammonium, paraquat, metribuzin, flumioxazin, ametryn, fluazifop-p-butil+fomesafen and atrazine), with two modes of application (with and without protection of the stem of the papaya plant). The application of herbicide was performed when plants had 0.70 m tall and for the treatments with protection of the stemwas used a polyethylene plate, placed beside the plant. At 7, 14, 21 and 35 days after application of herbicides were realized visual evaluations of weed control by species. At 45 days after application was performed evaluation of dry matter of weeds. For the papaya crop, were realized visuals evaluations of intoxication at 7, 14, 21 and 35 days after application at 0, 21, 42 and 63 days after application were realized evaluations for plant height and stem diameter. The main species of weeds in the area were Commelina benghalensis and Digitaria sanguinalis. The herbicide atrazine has caused intoxication in papaya plants independent of stem protection. The application of the paraquat, ametryn, metribuzin, glyphosate and fluazifop-p-butil+fomesafen require the protection of the stalk of the papaya plant. The glyphosate was effective on the control of the weeds, except for C. benghalensis. The herbicide glufosinate-ammonium, paraquat, metribuzin, flumioxazin, ametryn and the mix fluazifop-p-butylated+fomesafen showed potential for use in papaya plant
Selectivity and efficacy of herbicides in papaya crop
Keywords: Carica papaya; weeds; driven application; Commelina benghalensis; Carica papaya; plantas daninhas; aplicação dirigida; Commelina benghalensis; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA